Dynamic Contrast Enhanced MRI Can Monitor the Very Early Inflammatory Treatment Response upon Intra-Articular Steroid Injection in the Knee Joint: A Case Report with Review of the Literature. - Boesen, M; Kubassova, O; Cimmino, M; Ostergaard, M; Taylor, P; Danneskiold-Samsoe, B; Bliddal, H (2011)
Dynamic contrast-enhanced MRI in inflammatory arthritis, especially in conjunction with computer-aided analysis using appropriate dedicated software, seems to be a highly sensitive tool for monitoring the early inflammatory treatment response in patients with rheumatoid arthritis. This paper gives a review of the current knowledge of the emerging technique. The potential of the technique is demonstrated and discussed in the context of a case report following the early effect of an intra-articular steroid injection in a patient with rheumatoid arthritis flare in the knee.